2007
DOI: 10.1042/bj20061062
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the Na+/H+ exchanger

Abstract: The mammalian NHE (Na+/H+ exchanger) is a ubiquitously expressed integral membrane protein that regulates intracellular pH by removing a proton in exchange for an extracellular sodium ion. Of the nine known isoforms of the mammalian NHEs, the first isoform discovered (NHE1) is the most thoroughly characterized. NHE1 is involved in numerous physiological processes in mammals, including regulation of intracellular pH, cell-volume control, cytoskeletal organization, heart disease and cancer. NHE comprises two dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
184
0
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(199 citation statements)
references
References 137 publications
2
184
0
13
Order By: Relevance
“…Original studies of NOX1 gene regulation suggested the presence of a short NOX1 splice variant with intrinsic H + channel activity (8), although this was later realized to be an artifact due to the formation of a stable loop within NOX1 mRNA (6). Intracellular acidification by NOX/DUOX activation may also induce the activation of Na + /H + exchangers (NHE), which are ubiquitously expressed and are critically involved in the regulation of cell volume and shape, and cell adhesion, migration, and proliferation (21,22). Therefore, cellular actions of NOX/DUOX may also include ROSindependent mechanisms.…”
Section: General Aspects Of Nox-dependent Signaling Production Of Celmentioning
confidence: 99%
“…Original studies of NOX1 gene regulation suggested the presence of a short NOX1 splice variant with intrinsic H + channel activity (8), although this was later realized to be an artifact due to the formation of a stable loop within NOX1 mRNA (6). Intracellular acidification by NOX/DUOX activation may also induce the activation of Na + /H + exchangers (NHE), which are ubiquitously expressed and are critically involved in the regulation of cell volume and shape, and cell adhesion, migration, and proliferation (21,22). Therefore, cellular actions of NOX/DUOX may also include ROSindependent mechanisms.…”
Section: General Aspects Of Nox-dependent Signaling Production Of Celmentioning
confidence: 99%
“…[3][4][5] NHE1, the housekeeping isoform of the Na Ć¾ /H Ć¾ exchanger, is ubiquitously distributed in most tissues and has an important role in the regulation of pH i by exchanging intracellular protons [H Ć¾ ] i for extracellular sodium [Na Ć¾ ] e . [6][7][8] The transformed cells and tumor cells differ from normal tissues in that they have constitutive NHE1 activity at resting pH i , resulting in an increased pH i . 1,9 Intracellular alkalinization induced by the activation of NHE1 in tumor cells has been shown to play key role in the maintenance and progression of the neoplastic state.…”
mentioning
confidence: 99%
“…Such animals usually have a rather sparse hair coat that increases the danger of epidermal injuries and, thus, includes the necessity of continous barrier repair. In this way, the proliferative properties of NHE-1 are of specific importance (Slepkow et al 2007;Hosogi et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The members of this group of plasma membrane intrinsic proteins are expressed ubiquitously in all tissues, activated by numerous growth factors and implicated in pH homeostasis, cell volume regulation and proliferation, or the adjustment of intracellular pH (e.g. Hachem et al 2003;Slepkow et al 2007;Koliakos et al 2008). In the keratinocytes, NHE-1 is essential for acidifying the lipid microdomains (lipid rafts; Wenneckes et al 2009) and very important for barrier repair or recovery (e.g.…”
Section: Introductionmentioning
confidence: 99%